2003
DOI: 10.1115/1.1625401
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis for Design of a High-Precision Electronic Opto-Mechanical System for Vehicle Delineation Detection on Highway

Abstract: We have developed a laser photodiode array based detection system that can non-intrusively detect delineations of vehicles on the highway. The U.S. Patent Office has recently approved a patent for this detection system. The system is built with low-cost off-the-shelf opto-mechanical components. The error sources from a system design point of view will be analyzed in this paper. Our study indicates that the frequency of pulsed laser diodes, computer-sampling rates, deviations in the angle of laser light and imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Errors arose from the timing difference in the gap between the recorded timestamps and the true timestamps due to discrete sampling of the laser sensor. These errors related to the vehicle speed and the update rate of the laser sensors [11]. When the update rate for the laser sensor is fixed, if the vehicle travels at a high speed, the result is lower sampled points for the detector.…”
Section: Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Errors arose from the timing difference in the gap between the recorded timestamps and the true timestamps due to discrete sampling of the laser sensor. These errors related to the vehicle speed and the update rate of the laser sensors [11]. When the update rate for the laser sensor is fixed, if the vehicle travels at a high speed, the result is lower sampled points for the detector.…”
Section: Simulationsmentioning
confidence: 99%
“…For instance, Cheng, Shaw et al developed a detection system utilizing a pair of retroreflective laser sensors [10]. However, the usage of these sensors may induce errors in practical implementation [11]. Li et al [12] and Atluri et al [13] developed detectors based on transmission-based laser sensors and delivered results with a high level of accuracy, but the proposed method is difficult to transform due to the lack of generalization ability.…”
Section: Introductionmentioning
confidence: 99%
“…The theory behind this technology is that laser receivers detect the absence and presence of single or dual laser beams to determine the "presence" of vehicles (Harlow and Peng, 2001, Abramson and Chenoweth, 2000, Scientific Technologies Inc., 2006. However, much of this work focused on the overhead laser sensor (Hussain, et al, 1993, Hussain, 1995, Tropartz, et al, 1999, Cheng, et al, 2000, Lin, et al, 2001, Wang, et al, 2003. Hussain et al developed a reflectionbased infrared laser system which transmits laser signals on the road and senses vehicles by receiving laser signals reflected back from vehicle exteriors, to monitor traffic (Hussain, et al, 1993, Hussain, 1995.…”
Section: Development Of a Sensor…mentioning
confidence: 99%
“…Their findings indicated that the product, built by MBB SensTech, could accurately differentiate vehicle types using infrared lasers. In 1995, researchers from the University of Victoria developed the automatic vehicle dimension measure system (AVDMS), employing the system used the Schwartz Electro-Optics Autosense 3 sensor (Cheng, et al, 2000, Lin, et al, 2001, Wang, et al, 2003. These sensors can detect the distance between the detector and the object to determine the presence, size, and shape of the vehicle.…”
Section: Development Of a Sensor…mentioning
confidence: 99%
See 1 more Smart Citation